Mauritius : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
Mauritius has been a success story since independence, moving from low income to uppermiddle-income status. Close public-private partnerships facilitated private sector-led growth in astable macroeconomic and institutional environment. The government implemented an activeindustrial policy to support private sector competitiveness while exploiting global trade nichescreated by preferential access arrangements. As a result, savings were high and reinvested indiversifying the economy. Starting as a mono-cropped, inward-looking economy, Mauritiusmoved toward an export oriented and diversified economy producing textiles, tourism, financialand ICT services. Mauritius is now at a crossroads. On the one hand, it can pursue a path where reinvigorated public investment boosts economic growth and reinforced public assistance enhancesredistribution. On the other hand, it can select a path where private sector identifies constraintsfor growth and the public sector is the enabling agent that removes them, ensuring that proceedsare adequately shared by targeted assistance and improved service delivery. The Systematic Country Diagnostic (SCD) is intended to assess the priorities of Mauritius to accelerate sustainable economic growth while improving the welfare of the less well off. The SCD aims to understand why income growth among the bottom 40 percent of the population has been low relative to the average income. The SCD also addresses how the rate and structure of aggregate growth can be improved to accelerate income growth among the bottom 40 percent of the population, as well as ensure that overall growth is sustainable.